Upaya Perlindungan Hukum Terhadap Korban Tindak Pidana Pencabulan Pada Anak - Ansor kosnah ahmad (Jurnal Perspektif Hukum, 2022)
Obscenity is an act related to sex that violates the norms of decency (decency). This can happen to a boy to a girl or a girl to a boy, and the sexual abuse itself can happen to the same sex as a boy to a boy or a girl to another girl. At this time there are many crimes of sexual abuse of children. Considering that children are the young generation and potential human resources, the children themselves should get a legal protection, therefore the perpetrators who commit sexual abuse of children must be subject to appropriate criminal penalties, according to what they have done. In Indonesia itself, juridical law is regulated in the Children's Special Law, namely Law no. 35 of 2014 amendments to Law No. 23 of 2002 on child protection. The existence of legal guidelines can make it easier to give punishment for perpetrators of sexual abuse themselves, considering where their actions have a bad impact that causes trauma to the victim and the family around the victim.